2015
DOI: 10.1002/2015gl064559
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon aerosol‐induced Northern Hemisphere tropical expansion

Abstract: Global climate models (GCMs) underestimate the observed trend in tropical expansion. Recent studies partly attribute it to black carbon (BC) aerosols, which are poorly represented in GCMs. We conduct a suite of idealized experiments with the Community Atmosphere Model version 4 coupled to a slab ocean model forced with increasing BC concentrations covering a large swath of the estimated range of current BC radiative forcing while maintaining their spatial distribution. The Northern Hemisphere (NH) tropics expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 40 publications
5
36
0
Order By: Relevance
“…The pattern of zonal‐mean temperature change (Figure e) does not directly match the change in zonal‐mean radiative heating (Figure f), indicating that thermodynamic adjustments and changes in circulation largely explain the changes in thermal structure, relative humidity, and cloud. The spatial pattern of zonal‐mean temperature change is very consistent with those shown in other coupled model experiments (Kovilakam & Mahajan, ; Sand et al, ; Yoshimori & Broccoli, ). The transport of heat into the NH midlatitude upper troposphere therefore appears to be a consistent dynamical adjustment in global models.…”
Section: Resultssupporting
confidence: 89%
“…The pattern of zonal‐mean temperature change (Figure e) does not directly match the change in zonal‐mean radiative heating (Figure f), indicating that thermodynamic adjustments and changes in circulation largely explain the changes in thermal structure, relative humidity, and cloud. The spatial pattern of zonal‐mean temperature change is very consistent with those shown in other coupled model experiments (Kovilakam & Mahajan, ; Sand et al, ; Yoshimori & Broccoli, ). The transport of heat into the NH midlatitude upper troposphere therefore appears to be a consistent dynamical adjustment in global models.…”
Section: Resultssupporting
confidence: 89%
“…This indicates that neither stratospheric ozone depletion nor the direct radiative impact of increasing greenhouse gases are major factors for the NH trends (consistent with Deser and Phillips []). Finally, we recall that neither ensemble includes time varying aerosols nor tropospheric ozone, and it is conceivable that these forcings might enhance the poleward shift or may have contributed to the SST trends themselves [ Allen et al , ; Kovilakam and Mahajan , ]. Nonetheless, when internal variability is taken into account, these additional forcings do not appear necessary, as several individual model runs are able to produce trends comparable to those in the reanalyses.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that heating in the midlatitudes relative to tropics and high latitudes results in a northward shift of the maximum meridional temperature gradient with a poleward shift in the tropospheric jet (e.g., Allen et al, ; Kovilakam & Mahajan, ). Allen et al () define “Expansion Index (EI),” as a measure of change in temperature gradient across the midlatitudes, and find it to be strongly correlated with tropical expansion metrics (Allen et al, ; Kovilakam & Mahajan, ). EI is defined as 2Δ T 30 − 60 −(Δ T 0 − 30 +Δ T 60 − 90 ), where Δ T 30 − 60 , Δ T 0 − 30 , and Δ T 60 − 90 represent the change in mass‐weighted average tropospheric temperature over the troposphere (850–300 hpa) against the NOAER experiment for the northern hemisphere midlatitudes, tropics, and high‐latitudes, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The error bars for each metric are estimated at the 95% confidence level based on a student's t test with an effective sample size ( N effective = N (1 − ρ )(1 + ρ ) −1 , where ρ is the lag one autocorrelation) to account for serial temporal correlation. All metrics indicate NH tropical expansion with increase in BC forcing (Kovilakam & Mahajan, ), but with little difference between CC and BC experiments. The error bars in Figures a and b show that the expansion metrics in CC and BC are statistically indistinguishable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation